Pensions and housing wealth: Quantitative data on market conditions for equity release schemes in the EU - Peter Hennecke; Pierluigi Murro; Doris Neuberger; Flaviana Palmisano (Universität Rostock, Institut für Volkswirtschaftslehre, 2017)
Equity release schemes (ERS) may provide pension insurance by liquidating owner-occupied residential property. This paper examines the available data on market conditions for such products in all EU member states to cluster countries. Need for ERS is measured by demographic pressure, risk of poverty for the elderly and pension adequacy. Feasibility of ERS is measured by property and mortgage market indicators. Comparing overall need and feasibility index values we find that market conditions are very heterogonous in EU member states. For instance, while the Netherlands and the UK exhibit favourable ERS conditions, the opposite applies for Germany and Ireland. Hungary and Italy lie in between.
Keywords: D1; G1; J1; R2; R3; 330; ageing; equity release; pensions; homeownership; housing; reverse mortgage